Principles of Metal Casting, Third Edition - Sahoo, Mahi; Sahu, Sam (McGraw-Hill Education, 2014)
Addresses the latest advances in the field such as melting, casting processes, sand systems, alloy development, heat treatment, and processing technologies. New chapters cover solidification modeling, casting defects, and zinc and zinc alloys. Detailed photographs, illustrations, tables, and equations are included throughout. Ideal for students and researchers in metallurgy and foundry science as well as foundry industry professionals, this authoritative guide provides all of the information needed to produce premium-quality castings.